The interplay between the formation of Chinese cordyceps and the characteristics of soil properties and microbial network - Qinghe Wang; Yapei Wang; Ting Li; Xiuwen Bao; Liying He; Lin Liu; Sijing Liu; Jing Bai; Han Zhang; Shuqi Niu; Jinlin Guo (Microbiology Spectrum)
ABSTRACT Understanding the interplay between soil properties and microbial communities is crucial for elucidating the ecological mechanisms driving Chinese cordyceps (CC) formation. However, few studies have explored the dynamic changes in soil properties and microbial communities at different stages of CC formation. This study presents a comprehensive investigation of soil properties and bacterial communities across the developmental stages of CC. Our results showed that the mummified host larvae-rearing soil (MS) stage exhibited the most pronounced fluctuations in critical soil parameters, including soil pH, organic matter, total phosphorus, available phosphorus, and potassium levels, suggesting heightened nutrient mobilization to support CC growth. Enzyme activities analysis further revealed that CC growth notably altered the activities of acid phosphatase and dehydrogenase in the soil during the MS stage. 16S rRNA high-throughput sequencing analysis revealed that as CC developed, both bacterial richness and the abundance of specific bacterial genera, particularly Dyella and Pseudomonas, increased. Furthermore, microbial network analysis indicated that the network became most complex and unstable during the MS stage. The formation of CC was closely linked to changes in soil properties and the characteristics of the bacterial network. Additionally, functional prediction analysis revealed a significant upregulation of chitinolytic function during the MS stage, highlighting its ecological function in CC development. These findings provide foundational data for understanding the mechanisms underlying CC formation and for optimizing artificial CC production to achieve higher yield and better quality.IMPORTANCEThis study elucidates the interactions between soil properties and microbial communities in regulating the growth and development of CC. Key findings include: (i) dynamic fluctuations in soil physicochemical properties during CC formation, with significant nutrient depletion during the MS stage; (ii) distinct microbial community succession, showing the highest network complexity but lowest stability during the MS stage; (iii) functional prediction revealed enhanced chemoheterotrophy and chitinolysis in MS, indicating microbial adaptive regulation. These results provide a theoretical foundation for deciphering the molecular mechanisms of CC formation and optimizing its production.